Theme and Rheme in Harry Styles' Song "Cherry": A Systemic Functional Linguistics Analysis - Muhammad Syafiq; Ariel Abenaya Simamarta; Tulus Maruli Purba; Nurlela Majrul; Teza Aditra Ginting (Ruang Kata, 2026)
This study explores the emotional landscape of Harry Styles’ 2019 track "Cherry" through the lens of Systemic Functional Linguistics (SFL). By applying the thematic framework established by Halliday and Matthiessen (2004), the research dissects the song’s lyrics to understand how Theme-Rheme organization shapes its narrative. The analysis systematically categorizes the various types of themes, specifically topical and interpersonal and examines their corresponding rhemes across every clause of the song. The findings highlight a strong reliance on unmarked topical themes paired with rhemes centered on mental processes. This linguistic pattern isn't just a technical coincidence; it grounds the song in a deeply personal, introspective space, reflecting Styles' internal struggle and memory. Furthermore, the frequent use of interpersonal themes highlights the speaker's emotional vulnerability and their direct, almost conversational address to the song's subject. By treating these lyrics as sophisticated linguistic artifacts, this study contributes to the growing body of research that applies SFL to contemporary pop music. Ultimately, the results suggest that the specific grammatical choices in "Cherry" are strategically deployed to foreground feelings of longing and relational loss. These choices do more than just tell a story; they provide the textual cohesion and emotional weight that give the song its lasting impact. Through this systematic analysis, "Cherry" is revealed to be a meticulously structured discourse of heartbreak, where the grammar itself works to amplify the intensity of the message (Halliday & Matthiessen, 2004).